Domestication patterns in common bean (Phaseolus vulgaris L.) and the origin of the Mesoamerican and Andean cultivated races - Chacón Sánchez, María I.; Pickersgill, B; Debouck, Daniel G. (Springer, 2005)
Chloroplast DNA polymorphisms were studied by PCR sequencing and PCR-restriction fragment length polymorphism in 165 accessions of domesticated landraces of common bean from Latin America and the USA, 23 accessions of weedy beans, and 134 accessions of wild beans covering the entire geographic range of wild Phaseolus vulgaris. Fourteen chloroplast haplotypes were identified in wild beans, only five of which occur also in domesticated beans. The chloroplast data agree with those obtained from analyses based on morphology and isozymes and with other DNA polymorphisms in supporting independent domestications of common bean in Mesoamerica and the Andean region and in demonstrating a founder effect associated with domestication in each region. Andean landraces have been classified into three different racial groups, but all share the same chloroplast haplotype. This suggests that common bean was domesticated once only in South America and that the races diverged post-domestication. The haplotype found in Andean domesticated beans is confined to the southern part of the range of wild beans, so Andean beans were probably domesticated somewhere within this area. Mesoamerican landraces have been classified into four racial groups. Our limited samples of Races Jalisco and Guatemala differ from the more widespread and commercially important Races Mesoamerica and Durango in types and/or frequencies of haplotypes. All four Mesoamerican races share their haplotypes with local wild beans in parts of their ranges. Independent domestications of at least some of the races in Mesoamerica and/or conversion of some locally adapted wild beans to cultigens by hybridization with introduced domesticated beans, followed by introgression of the “domestication syndrome” seem the most plausible explanations of the chloroplast and other molecular data.